Profesionalisme Guru Dalam Pembelajaran - Sofia Azhar (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2013)
This journal discusses about the definition of teacher’s professionalism and the teaching, the terms of a professional teacher, the teacher’s performance, the ten qualities of the good teacher, the six of successful teacher’s characters, the unfortunate teacher’s character, the ten of teacher’s mistakes, the problem or difficulty of the teacher in learning